Characterization of titania thin films grown by dip-coating technique - Dastan, Davoud; Panahi, Seyedeh Leila; Chaure, Nandu B. (Journal of materials science. Materials in electronics, 2016)
A dip-coating technique was employed to prepare anatase phase of titania thin films. Fluorine doped tin oxide substrates were used to prepare titania thin films. The samples were annealed at 550 °C for 18 h. X-ray diffraction results revealed the amorphous and anatase phases of TiO 2 for as-synthesized and annealed samples, respectively. The crystallite size of anatase TiO 2 thin films was almost 25 nm for annealed samples. UV–visible confirmed the energy band gap 3.86 and 3.64 eV for as-prepared and calcinated titania thin films. The reduction in the energy band gap could be due to the change in crystallization and agglomeration of small grains after calcination. The morphology of the prepared films was investigated by field emission scanning electron microscopy which demonstrated the agglomeration of spherical particles of TiO 2 with average particle size of about 30 nm. The molecular properties (chemical bonding) of the samples were investigated by means of Fourier Transform Infrared (FTIR) spectroscopy. FTIR analysis exhibited the formation of titania, functional group OH, hydroxyl stretching vibrations of the C–OH groups, bending vibration mode of H–O–H, alkyl C–H stretch, stretching band of Ti–OH, CN asymmetric band stretching, and C=O saturated aldehyde.